Leishmania spp Infection in Patients and Great Gerbils (Rhombomys opimus) in a High-Risk Focus of Zoonotic Cutaneous Leishmaniasis in Central Iran: a Microscopic and Molecular Survey - Narges Marvi Moghadam; Mehdi Mohebali; Yavar Rassi; Ali Reza Zahraei-Ramazani; Mohammad Ali Oshaghi; Reza Jafari; Mahboubeh Fatemi; Mohammad Hossein Arandian; Hamid Abdoli; Nilufar Shareghi; Maryam Ghanei; Nilufar Jalali-Zand; et al. (Journal of Arthropod-Borne Diseases)
Background: Zoonotic cutaneous leishmaniasis (ZCL) is an endemic disease in Varzaneh City where Leishmania major is the causative agent and the great gerbil, Rhombomys opimus, is the main reservoir host of the disease. Despite control efforts, ZCL outbreaks recur every few years. This study was conducted to revive information on the parasite/s species circulating between humans and the reservoirs in the region. Methods: Leishmania infection in patients and R. opimus was studied using direct parasitological and molecular methods during 2019–2021. Nested-PCR and DNA sequencing were used for Leishmania parasite identification. Inter and intra-species variations in the Leishmania parasites were investigated using BLAST and MEGA7 software. Results: All suspected patients (N=34) and 14 out of 36 great gerbils tested positive for Leishmania parasites via direct parasitological method. Nested-PCR method revealed all the patients were infected with L. major (94.1%) and mixed infection of L. major and Leishmania turanica (5.9%), and great gerbil specimens were infected with either L. major (44.4%), L. turanica (5.6%), or Leishmania gerbilli (5.6%) and also with mixed infection of L. major and L. turanica (30.5%), L. major and L. gerbilli (8.3%) and mix of all the three Leishmania species (5.6%). Conclusion: The identical sequences of L. major in both human patients and rodents indicate that the great gerbils are the main reservoirs of L. major in Varzaneh City. The presence of L. turanica in patients would be of interest to carry out further studies to determine the role of this species in the persistence, signs, and treatment of ZCL in humans.